PENINGKATAN KETERAMPILAN MENULIS ARGUMENTASI MELALUI MODEL THINK PAIR SHARE DAN MEDIA AUDIOVISUAL PADA SISWA KELAS X-10 SMA NEGERI KEBAKKRAMAT - Fitria Cahyaningrum; Andayani Andayani; Kundharu Saddhono (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2018)
This research aims to improve learning process quality of writing argumentation text and argumentation writing skills through the Think Pair Share model with audiovisual media of students X-10 grade SMA Negeri Kebakkramat. This research was a Classroom Action Research (CAR) with two cycles. Data sources include events, informants, and documents. Data collection through interviews, observation, and document analysis. Data validity by triangulation method technique, triangulation of data source and informant review. Data analysis technique using comparative descriptive analysis technique. Think Pair Share model with audiovisual is able to improve the quality of learning process of argumentation writing skill indicated by teacher and student performance. In pre-cycles, the teacher and student performance values were still below the achievement indicator. In cycle I, the value of teacher performance increased to 69.29 and the percentage of student performance of 47.22%. Meanwhile, in cycle II the teacher performance value became 80.71 and the percentage of student performance became 78.95%. After the action done on the first cycle, there were only 21 students who achieved the value of KKM (minimum completeness criteria) which means it did not meet the achievement indicators. Implementation of Think Pair Share with audiovisual media in cycle II showed a significant improvement in argumentation writing skill, that is, score of 31 students exceeded KKM. In conclusion, the application of Think Pair Share model with audiovisual media is able to improve learning process quality and argumentation writing skill for the tenth grade students of SMA Negeri Kebakkramat.Â AbstrakPenelitian ini bertujuan untuk meningkatkan kualitas proses pembelajaran menulis argumentasi dan keterampilan menulis argumentasi melalui penerapan model Think Pair Share dengan media audiovisual siswa kelas X-10 SMA Negeri Kebakkramat. Penelitian ini adalah Penelitian Tindakan Kelas dengan dua siklus. Sumber data berupa peristiwa, informan, dan dokumen. Pengumpulan data melalui wawancara, observasi, dan analisis dokumen. Validitas data dengan teknik triangulasi metode, triangulasi sumber data dan review informan. Teknik analisis data menggunakan teknik analisis deskriptif komparatif. Model Think Pair Share dengan audiovisual mampu meningkatkan kualitas proses pembelajaran keterampilan menulis argumentasi dengan indikator kinerja guru dan siswa. Pada prasiklus, nilai kinerja guru dan siswa masih berada di bawah indikator pencapaian. Siklus I, nilai kinerja guru meningkat menjadi 69,29% dan kinerja siswa sebesar 47,22% sedangkan pada siklus II nilai kinerja guru menjadi 80,71% dan kinerja siswa menjadi 78,95%. Setelah dilakukan tindakan pada siklus I, siswa yang tuntas hanya 21 siswa yang artinya dianggap belum memenuhi indikator pencapaian. Penerapan Think Pair Share dengan media audiovisual pada siklus II, menunjukkan peningkatan signifikan pada keterampilan menulis argumentasi, yaitu skor 31 siswa melampaui KKM. Disimpulkan bahwa penerapan model Think Pair Share dengan audiovisual mampu meningkatkan kualitas proses dan keterampilan menulis argumentasi pada siswa kelas X SMA Negeri Kebakkramat.